# How do you solve # (x-6)^2 = 25#?

Either #{: (,(x-6)+5 = 0, ," or ",,(x-6)-5=0), (rArr,x-1=0, , , ,x-11=0), (rArr,x=1, ," or ", ,x=11) :}#

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (x-6)^2 = 25:

- Expand the left side of the equation: (x-6)^2 = (x-6)(x-6) = x^2 - 12x + 36.
- Set the expanded expression equal to 25: x^2 - 12x + 36 = 25.
- Rearrange the equation by subtracting 25 from both sides: x^2 - 12x + 36 - 25 = 0, which simplifies to x^2 - 12x + 11 = 0.
- Factor the quadratic equation: (x - 11)(x - 1) = 0.
- Set each factor equal to zero and solve for x:
- x - 11 = 0 => x = 11
- x - 1 = 0 => x = 1.

So, the solutions to the equation are x = 11 and x = 1.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7